Front Cover: Probing the Interfaces in Nanosilica‐Supported TiO2 Photocatalysts by Solid‐State NMR and In Situ FTIR (ChemNanoMat 12/2018). Issue 12 (20th November 2018) - Singh, Rustam; Bayal, Nisha; Maity, Ayan; Pradeep, D. Jeiyendira; Trébosc, Julien; Madhu, P. K.; Lafon, Olivier; Polshettiwar, Vivek
Abstract : The ammonia‐assisted functionalization of DFNS by titanium butoxide involves several step‐wise surface reactions, including silanol deprotonation, and then its hetero‐condensation with titanium hydroxide generating Si‐O‐Ti oxobridges. Then the oxy‐anion of titanols condense with another molecule of ammonia‐activated titanium hydroxide to generate Ti‐O‐Ti oxobridges, and these steps repeat to produce amorphous Ti‐O‐Ti network, which on thermal heating yields DFNS/TiO2 photocatalysts via the condensation of titanols. 1 H, 29 Si, 47, 49 Ti NMR and in‐situ IR study confirmed the proposed mechanism of DFNS/TiO2 catalysts and provided insights into the photocatalytic interfaces between nanosilica and TiO2 surfaces. More information can be found in the Full Paper by Olivier Lafon, Vivek Polshettiwar et al. onpage 1231 in Issue 12, 2018 (DOI:10.1002/cnma.201800338 ).